Structural, optical and magnetic chatacterization of spinel zinc chromite ZnCr2O4) nanocrystals synthesized by thermal treatment method - Gene, Adamu Salahudeen (2014)
Spinels and spinel-like materials are subjects of continuing study in materials sciences because their physical and chemical properties have a wide range of applications. In particular, zinc chromite (ZnCr2O4) nanocrystals are commonly used in catalysis and humidity sensors, on top of their main usage as magnetic material for devices. Various methods have been applied for the synthesis of spinels ZnCr2O4 including the mechanical activation, chemical, microwave, sol-gel, ball milling, combustion methods,among others, but most of these methods are difficult to employ on a large scale production because of their complicated procedures, longer reaction times, high reaction temperatures, toxic reagents and by-products which are potentially harmful to the environment. In this study the spinel ZnCr2O4 nanocrystals were first time synthesized by means of thermal treatment method from an aqueous solution containing only zinc and chromic nitrates, poly(vinyl pyrrolidone), and deionized water. The solution was dried at 353 K for 24 h before grinding and calcination at temperatures ranging from 773 to 973 K to remove unwanted polymer and crystalize the material. The characterization studies of ZnCr2O4 nanocrystallines were carried out by X-ray Diffraction spectroscopy (XRD), Electron Dispersive X-ray spectroscopy (EDX), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FT-IR), UV-Vis Spectrometer, and Electron Spin Resonance Spectroscopy (ESR). The corresponding peaks of Zn, Cr and O were observed in the EDX analysis of the sample which confirms the formation of ZnCr2O4. The XRD patterns confirmed the formation of the single faced nanocrystallines of spinel ZnCr2O4 with a face-centered cubic structure. The average particle size of the synthesized nanocrystals was also determined by XRD using theSch erer’s formula and was in good agreement with the TEM images which shows cubical zinc chromite (ZnCr2O4) nanoparticles with uniform morphology and particle size distributions. The results of XRD and TEM showed that the particle size increased with the calcination temperature increases from 19 nm at 773 K to 24 nm at 973 K. The FT-IR spectra showed only two principle absorption bands of Cr-O and Zn-O located at 490 and 615 cm−1 respectively, indicating the calcined samples are very pure. The band gap energy was determined from UV-vis reflectance spectra using the Kubelka-Munk function and the band gaps were found to decrease with increase in calcination temperature from 4.03 eV at 773 K to 3.89 eV at 973 K due to particle size increased. The magnetic properties measured by ESR confirmed the existence of unpaired electrons and the resonant magnetic field and the g-factor of the calcined samples were measured. The g-factor was found to increase from 1.9598 to 1.9616 and the resonant magnetic field (Hr) decreased from 3.3468 10-7 to 3.3437 10-7 A/m as the calcination temperature increases from 773 to 973 K respectively.